Nightmares! : the lost lullaby - Segel, Jason, 1980-; Miller, Kirsten, 1973- (Segel, Jason, 1980- Nightmares! (Series, 2016)
"Twelve-year-old Charlie and his friends are in new danger as a visitor from the Netherworld is in Cypress Creek and is intent upon connecting the two worlds. It is up to them to stop that from happening or risk losing all that they've ever known"--